Brefeldin A affects adhesion of zoospores of the green alga Enteromorpha - Callow, M E (Journal of experimental botany, 2001)
Primary adhesion of zoospores of the green macroalga Enteromorpha to substrata involves a massive release of adhesive glycoproteins from Golgi-derived, membrane-bounded vesicles in the anterior region of the spore, followed by rapid curing. This process is sensitive to low concentrations (5-10 microg x ml(-1)) of the secretion-inhibiting antibiotic, brefeldin A (BFA). The proportion of cells that settled in BFA was reduced by approximately 50%, but the effect was fully reversed by washing in seawater to remove the BFA. Ultrastructural observations showed that BFA caused the breakdown of Golgi stacks in the majority of cells examined. When settled cells were subjected to shear stress, a greater proportion of those settled in the presence of BFA were detached, compared with controls, indicating reduced adhesion strength in the presence of the antibiotic. The most likely reason for this is that strong adhesion to substrata either requires the synthesis of extra adhesive materials beyond those present in the swimming spore, or the secretion of an additional component required for adhesive curing. The novel use of atomic force microscopy in force modulation mode demonstrated that the adhesive secreted by most spores in the presence of BFA did not undergo the rapid curing process typical of control spores. However, some variation between zoospores was observed, with some cells showing no ultrastructural changes and normal adhesive curing. These results are discussed in relation to variations observed in the propensity and competence of spores to settle, which may be reflected in differential requirements for de novo synthesis and secretion of materials needed for full adhesion